PANCASILA AND CITIZENSHIP EDUCATION FOR BORDER COMMUNITIES AND INDONESIA'S OUTERMOST REGIONS - Ferdiansyah, Mohamad Ferli; Timur, Fauzi Gustarina Campaka; Sumarno, Ari Pitoyo (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2023)
Indonesia as an archipelagic country has several border areas both on land (continental) and sea (maritime) borders. Nationalism in border and underdeveloped areas is very important to maintain the unity and integrity of the Republic of Indonesia because border areas are locations or areas that are very vulnerable to the fading of feelings and attitudes of nationalism. One of the efforts to foster a sense of nationalism in border areas is through Pancasila and Citizenship education which is expected to reduce the occurrence of unresolved socio-political, security and cultural problems in border areas. In any situation and condition, the cultivation of Pancasila values and a sense of love for the country will make it easier for people in border areas not to get entangled with conflicts that will arise or conflicts that already exist. The purpose of this research is to analyze Pancasila and citizenship education for border communities and Indonesia's outermost regions. This research uses a literature study research method. The results of this study show that education with the concept of citizenship focuses on the involvement of students to learn actively, participate in school or the surrounding community. As a young citizen in the border region, you must understand, realize, and make the content of your conscience to love and act in defending and developing your identity based on Indonesian values, namely Pancasila, the 1945 Constitution of the Republic of Indonesia, and Bhinneka Tunggal Ika.